Development of iBeacon application 2 & 3 - Khong, Nicholas Farn Ming (Nanyang Technological University, 2022)
During the Covid-19 pandemic, most lessons are conducted online using tools such as Zoom and Microsoft Teams to minimise the spread of the virus. During these lessons, it is observed that students are more engaged with the professor in the chat as compared to physical lessons. As physical lessons are resuming for NTU, we want to continue having students be proactive and ask questions to the professor so that it can better enhance the learning experience for other students as well. This project aims to develop a mobile application utilising beacon technology to enhance the learning experience for students and to promote a Smart Campus at the same time. The application will consist of three core beacon functions, close-proximity information sharing, and public and private chatrooms, which aim to connect users within a close-proximity range. By using the application, the class chatroom function will allow students to pose questions to the professors at any time without disturbing the class, while the public chatroom function allows users to socialise with others in common areas within NTU. The close-proximity information-sharing functions will allow NTU event organizers to share information with their targeted audiences easily with this application. Currently, the app is completed with all the functions tested and working as intended and satisfying all the objectives. The adoption of this application in NTU will bring NTU even closer to being a smart campus.